Peri-Urban and Urban Agriculture in Constantine, Algeria - Assia Lifa (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2024)
This study focuses on the metropolitan area of Constantine, a territory of regional attraction, capable of stimulating the development of the wilaya in the coming years thanks to a diversified and multifunctional peri-urban agriculture. The study is based on a questionnaire survey carried out throughout the study area. Specifically in the municipalities of Hamma and Khroub, the results show that, despite the progression of urbanization, the Constantine Urban Group contributes 37% of the total production of the wilaya in 2022. This production is characterized by a certain diversity: cereal crops, market gardening and arboriculture are the pillars of agriculture in Constantine. Beyond its primary vocation, this agriculture contributes to the attractiveness of territories and landscapes that reflect the image of the city, to the management and protection of natural resources, while shaping rural landscapes”.